School Heads’ Educational Leadership Practice and Teachers’ Performance: The Case of Omar District, Division of Sulu, Philippines - Abdurahman, Norman A.; Jul-Aspi K. Omar (HM Publisher, 2021)
The objective of the study was to determine the school heads’ educational leadership practice and teachers’ performance in Omar District, Division of Sulu, Philippines. The respondents of the study were 82 elementary school teachers and 15 school heads. A structured questionnaire was used to gather the needed data. The statistical used were frequency counts, percentage, weighted mean and ANOVA. The result of the study revealed that the majority of the teachers were female, with an age ranged from 31-40 old, and have been rendering service for two years and above. Further, the teachers were very satisfactory in terms of their performance on lesson planning delivery, assessment, and management of time and learning environment, and technical assistance. Meanwhile, they were also very satisfactory in terms of professional and personal characteristics. In the same vein, school heads have outstanding performance in terms of assessment of themselves, about their relationship with others, about their job and about their beliefs on the concept of life. While they have a very satisfactory performance in terms of their personal and professional characteristics such as decisiveness, honesty, dedication/ commitment, initiative/ resourcefulness, courtesy, human relations, leadership, stress tolerance, fairness, and good grooming. Moreover, there was no significant difference of teachers’ performance in terms of age, gender and length of service. And there was no significant difference on the level of teachers’ performance in terms of lesson planning delivery, assessment, management of time and learning environment and technical assistance as rated by the school heads and teachers themselves. On the basis of the aforementioned findings, the following recommendations are hereby advanced: first, the elementary school teachers need for a continuing professional development through pursuing graduate schooling or attending in-service trainings, seminars, symposia and the like. Second, the school administrators may upgrade their technical, human, and administrative skills to keep pace with educational advancement through executive training.